Glycemic Status and Its Impact on Clinical Profile and Outcomes in Tuberculosis Patients: A Hospital-Based Prospective Study in Nepal - Bam, Niraj; Ghimire, Prajwal Ram; Shrestha, Bibek; Ayer, Nabin (Journal of College of Medical Sciences-Nepal, 2025)
Background Tuberculosis (TB) and diabetes mellitus (DM) are increasing comorbidities in low- and middle-income countries, affecting diagnosis, treatment, and prognosis. Methods A hospital-based prospective cohort study was conducted at Tribhuvan University Teaching Hospital, Kathmandu, from July 2023 to August 2024. A total of 140 adult TB patients (≥18 years) were enrolled and followed until the intensive phase of anti-tubercular therapy. DM was diagnosed using American Diabetes Association criteria. Clinical features, laboratory results, and treatment outcomes were compared between TB patients with and without DM. Results DM was found in 33 patients (23.6%), most with disease duration <5 years. Diabetic patients were older (mean 56.5 vs. 46.1 years, p-value<0.001) and reported less weight loss (33% vs. 60%, p-value=0.009). Mean adenosine deaminase levels were lower in diabetics (20.9 vs. 37.9 IU/L, p-value=0.043). Hospital stay was longer in diabetics (12.7 vs. 9.3 days, p-value=0.004). Sputum conversion at two months was lower in diabetics but not significant (78.6% vs. 95.9%, p-value=0.068). Peripheral neuropathy was more frequent in diabetics (18% vs. 4%, p-value=0.010). No significant differences were observed in radiological patterns or other adverse drug reactions. Conclusions DM is common among TB patients in Nepal and is linked to distinct clinical features, lower ADA levels, prolonged hospitalization, and higher neuropathy risk. Bidirectional screening and optimal glycemic control may improve TB outcomes.